2020
DOI: 10.1080/15384101.2020.1731645
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long noncoding RNA LINC00657 enhances the malignancy of pancreatic ductal adenocarcinoma by acting as a competing endogenous RNA on microRNA-433 to increase PAK4 expression

Abstract: A long noncoding RNAs (lncRNA) called LINC00657 is dysregulated and contributes to tumor progression in a number of human cancer types. However, there is limited information on the expression profile and functions of LINC00657 in pancreatic ductal adenocarcinoma (PDAC). The expression profile of LINC00657 in PDAC was estimated by reverse-transcription quantitative polymerase chain reaction (RT-qPCR). The effects of LINC00657 upregulation on PDAC cell proliferation, apoptosis, migration, and invasion in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…For example, lncRNA PVT1 sponged miR-519d-3p to promote progression and glycolysis in pancreatic ductal adenocarcinoma (PDAC) [ 7 ]. LncRNA LINC00657 facilitated the malignancy of PDAC via regarding as a competing endogenous RNA (ceRNA) on miR-433 to upregulate PAK4 expression [ 8 ]. Additionally, lncRNA ITGB2-AS2 has been discovered to accelerate cell proliferation and aggressiveness via regulating miR-4319/RAF1 in PDAC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNA PVT1 sponged miR-519d-3p to promote progression and glycolysis in pancreatic ductal adenocarcinoma (PDAC) [ 7 ]. LncRNA LINC00657 facilitated the malignancy of PDAC via regarding as a competing endogenous RNA (ceRNA) on miR-433 to upregulate PAK4 expression [ 8 ]. Additionally, lncRNA ITGB2-AS2 has been discovered to accelerate cell proliferation and aggressiveness via regulating miR-4319/RAF1 in PDAC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the correlation of NORAD expression with OS in cancer patients, a total of 14 articles with 867 subjects were enrolled in the present analysis [19-27,33-37]. The overall results showed that elevated level of NORAD was significantly related to worse prognosis (HR = 1.46, 95% CI: 1.06-2.01, P = 0.020) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated that high NORAD expression acted as a competitive endogenous RNA (ceRNA) by sponging miRNA to regulate target genes of miRNA, and thereby exerted its oncogenic role [19,21,26,[37][38][39][40][41][42]. For instance, it was demonstrated that NORAD positively regulated JunB expression via serving as a ceRNA to sponge miR-615-3p, and then contributed to ESCC progression [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PC, the expression of lncRNAs are often maladjusted, for example lncRNA HULC is abnormally increased in PC, and its high expression is signi cantly related to metastasis and vascular invasion of PC [16]. In addition, lncRNA PVT1 upregulates the progression and glycolysis of PC cells by regulating mir-519d-3p and HIF1α, and LINC00657 acts as a miR-433 sponge to enhance the malignancy of pancreatic ductal adenocarcinoma [17,18]. Although lncRNA plays a decisive role in PC, the study of LINC01094 in PC has not been reported, and the interaction between LINC01094 and miRNA remains unclear.…”
Section: Introductionmentioning
confidence: 99%